Legacy Core Modernization via Strangler-Fig with Micro Frontends: Risk-Reduced Migration Patterns: A Case Study with Defect/Incident Deltas - VijayKumar Pasunoori (International Journal of Computational and Experimental Science and Engineering, 2026)
Legacy core systems present significant challenges to enterprise organizations through operational inefficiencies, limited scalability, and constraints on digital innovation. Traditional big-bang replacement strategies carry substantial risks including extended timelines, high failure rates, and business disruption. Incremental modernization patterns offer viable alternatives by enabling gradual transformation while maintaining operational continuity. The strangler-fig pattern facilitates backend evolution through progressive routing of requests from legacy components to modern services. Micro frontend architectures complement this by decomposing monolithic user interfaces into independently deployable modules aligned with business domains. Anti-corruption layers prevent architectural degradation by translating between legacy and modern system semantics. Together, these patterns enable controlled technical debt management, fault isolation, and continuous value delivery. Organizations adopting these incremental strategies experience reduced deployment risks, improved system performance, enhanced team autonomy, and better incident containment. The architectural decomposition supports parallel development streams, accelerates delivery cycles, and maintains production stability throughout transformation initiatives. This evolutionary modernization framework provides enterprises with practical pathways to replace decades-old systems while preserving business continuity and institutional knowledge.